The Role of Dynamic Capability Toward Knowledge Management, Innovation, Technology Information of 3PL Provider Indonesia - Widiadibrata, Sri Witjaksono; Nawangsari, Lenny Christina; Sutawidjaya, Achmad Hidayat (International Journal of Supply Chain Management, 2021)
In a highly competitive global economy, every company depends on how much innovation and creativity it has. This study aims to analyze the effect of Knowledge Management, Innovation, Information Technology on Dynamic Capabilities for two groups; the first group is 3PL Provider in Jakarta and group 2 is the 3PL provider from outside Jakarta. The research sample is 200 people. The data analysis technique used Structural Equation Modeling (SEM), with PLS (Partial Least Square) software. The study results prove that Knowledge Management, Innovation, and Information Technology affect the Dynamic Capability of 3PL Providers in Jakarta and outside Jakarta.